PRIRES education program: Risk prevention program of social networks - Avilés Martínez, José María (2014)
The article offers a reflection on the underlying processes of moral character to the interpersonal relations that are brought into play in the school day-to-day life in general and in situations of peer violence (bullying and cyberbullying) in particular. It presents the educational program PRIRES so as to work these processes in the school community.